2023
DOI: 10.1097/sla.0000000000006059
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Reviews and Meta-analyses of the Procedure-specific Risks of Thrombosis and Bleeding in General Abdominal, Colorectal, Upper-Gastrointestinal and Hepatopancreatobiliary Surgery

Lauri I. Lavikainen,
Gordon H. Guyatt,
Ville J. Sallinen
et al.

Abstract: Objective: To provide procedure-specific estimates of symptomatic venous thromboembolism (VTE) and major bleeding following abdominal surgery. Summary Background Data: Use of pharmacological thromboprophylaxis represents a trade-off that depends on VTE and bleeding risks that vary between procedures; their magnitude remains uncertain. Methods: We identified observational studies reporting procedure-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…Although prior work exists on procedure-specific risks of thrombosis and bleeding in surgery (with variable certainty evidence), 27 , 28 , 29 , 30 , 31 , 32 , 33 the optimal starting time and duration of thromboprophylaxis remains unclear owing to insufficient statistical power of existing randomized trials in the field and the changing nature of surgery (eg, earlier mobilization and less-invasive surgery). 34 , 35 This has contributed to substantial practice variation in thromboprophylaxis worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Although prior work exists on procedure-specific risks of thrombosis and bleeding in surgery (with variable certainty evidence), 27 , 28 , 29 , 30 , 31 , 32 , 33 the optimal starting time and duration of thromboprophylaxis remains unclear owing to insufficient statistical power of existing randomized trials in the field and the changing nature of surgery (eg, earlier mobilization and less-invasive surgery). 34 , 35 This has contributed to substantial practice variation in thromboprophylaxis worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients undergoing RIS, both surgery and chemotherapy were previously reported risk factors for VTE. 29 , 30 Thus, the perioperative period is of special interest. In our data, postoperative VTE incidence at 3 months following surgery stood at 2.0%.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta‐analysis reported that the estimated four‐week postoperative risk of symptomatic VTE without thromboprophylaxis was 6.2% following an open pancreatoduodenectomy for benign and malignant indications; yet, that estimate was deemed to have a low level of certainty. 29 A US prospective single‐center study found that among pancreatic adenocarcinoma patients undergoing either curative or palliative surgery exhibited a 12% postoperative cumulative incidence of VTE at 3 months following surgery despite thromboprophylaxis lasting for 21 days post‐operatively. 30 While the specific stage distribution was not reported, 9% had metastatic disease and the pre‐operative chemotherapy rate of 14.5% was similar to our data.…”
Section: Discussionmentioning
confidence: 99%
“… b Net benefit is equal to absolute reduction in VTE risk minus absolute increase in bleeding risk (with twice the weight for major bleeding as for VTE). Net benefit with prophylaxis assumes an approximately 50% decrease in VTE and an approximately 50% increase in major bleed based on meta-analysis by Gould et al 5 and updated by Lavikainen et al 6 …”
Section: Recommendationmentioning
confidence: 99%
“…Explanation: High-quality evidence found that LMWHs significantly reduce the risk of VTE compared with no anticoagulation. 2 , 6 , 11 In the absence of direct comparisons between LMWH and DOAC, and between DOAC and no anticoagulation among patients undergoing urological surgery, evidence from a systematic review and network meta-analysis suggests the efficacy and safety of DOACs is comparable to LMWH. 11 Some caution may be considered among postoperative patients who are expected to have decreased gastric motility or ileus.…”
Section: Recommendationmentioning
confidence: 99%